I IMPLIMENTASI NILAI-NILAI KARAKTER DI SD NEGERI 12 SAMALANGA - Misrina Misrina (PGMI IAIN Lhokseumawe, 2022)
Character values ​​are values ​​that must be formed in each individual. To develop these character values, habituation and example are needed. The purpose of this research is to find out how the character values ​​are implemented in SD Negeri 12 Salamanga. This research is a qualitative research . The data analyzed in this study are data from observations and interviews. The data sources set in this study consisted of 2 people, namely the principal and the teacher. The results showed that the implementation of character values ​​in SD Negeri 12 Samalanga had been carried out well. The implementation of character values ​​is carried out both through learning activities and activities outside of learning.